The Role and Current Status of IFRS in the Completion of National Accounting Rules – Evidence from the UK. (4th May 2017) - Collis, Jill; Jarvis, Robin; Skerratt, Len
Abstract: Drawing on secondary data, we examine the transposition of the Accounting Directive 2013 into UK GAAP with a specific focus on references to IFRS. The process involved consultation and regulatory impact assessment on the options in the Accounting Directive and proposed changes to accounting standards for non-publicly accountable entities. This led to an IFRS-based approach from 2016 with three tiers: EU-adopted IFRS for group listed companies and other publicly accountable entities, an adaptation of IFRS for SMEs for non-publicly accountable entities, and a simplified version for micro-entities incorporating the requirements of the Accounting Directive. This outcome is not surprising since the UK was one of the founding members of the original International Accounting Standards Committee and a strong proponent of little GAAP. Indeed, the UK's former Financial Reporting Standard for Smaller Entities provided a model for the IFRS for SMEs. In the past, there were few references to IFRS by the UK's enforcement and interpretation bodies. Today, guidance is taken from IFRS Interpretations Committee. We contribute to the literature by describing the main processes involved in implementing the Accounting Directive and the move to an IFRS-based approach in UK GAAP. Our analysis should be of interest to researchers and policymakers alike.